Sverdlovsk Region Industry and Its Consumer Market in “Dashing” 1990s: Mysteries and Paradoxes of Reform Era (according to Regional Statistics of 1992-2000) - V. N. Mamyachenkov; V. S. Plokhotnikov (Научный диалог)
The aim of the study is to analyze the state of industrial production in the Sverdlovsk region in the 1990s and its impact on the provision of population with consumer goods. The topic is relevant in the context of studying the impact of the crisis on the financial situation of population. The study was conducted on the materials provided by the Territorial body of the Federal State Statistics Service, with the involvement of scientific and journalistic literature on this issue. It is argued that the fall in production in the 1990s was caused by the collapse of the decades-old system of economic relations within the USSR and the Council of economic mutual assistance, as well as the reduction of purchases of materials and components from Western countries. It is declared that the decline in production in all industries of the Sverdlovsk region without exception continued until 1999. It is noted that after 1998 the industry of the region began to rise in all its branches, except for fuel. It is proved that the state of the consumer market in the segment of industrial goods for population did not correlate with the dynamics of their production in the region. It is concluded that the deep crisis of industrial production, which lasted until the end of the 1990s, in the market of consumer goods was largely compensated by imports of foreign consumer goods.